Modulation in Biofertilization and Biofortification of Wheat Crop by Inoculation of Zinc-Solubilizing Rhizobacteria - Yadav, Ramesh Chandra; Sharma, Sushil K.; Varma, Ajit; Rajawat, Mahendra Vikram Singh; Khan, Mohammad Shavez; Sharma, Pawan K.; Malviya, Deepti; Singh, Udai B.; Rai, Jai P.; Saxena, Anil K. (Frontiers in Plant Science, 2022)
Zinc is an important micronutrient needed for the optimum growth and development of plants. Contrary to chemical zinc fertilizers, the use of zinc solubilizing bacteria is an environmentally friendly option for zinc enrichment in edible parts of crops. The present study was conducted with the objective to select potential zinc solubilizing rhizobacteria from rhizosphere of chickpea grown in soils of eastern Uttar Pradesh and to further assess their impact on the magnitude of zinc assimilation in wheat crop. Among the 15 isolates, CRS-9, CRS-17, CRS-30 CRS-38 produced net soluble zinc in broth to the tune of 6.10, 5.90, 5.63 and 5.60 μg ml-1, respectively, in zinc phosphate with corresponding pH being 4.48, 5.31, 5.20 and 4.76. However, the bacterial strains CRS-17, CRS-30, CRS-38 and CRS-9 showed maximum zinc phosphate solubilization efficiency of 427.79, 317.39, 253.57 and 237.04%, respectively. The four bacterial isolates were identified as Bacillus glycinifermentans CRS-9, Microbacterium oxydans CRS-17, Paenarthrobacter nicotinovorans CRS-30 and Bacillus tequilensis CRS-38 on the basis of morphological and biochemical studies and 16S rRNA gene sequencing. Bacterial inoculants significantly colonized the roots of wheat plants and formed biofilm on the root matrix. These strains were significantly increased the seed germination (%) and vigour indices in wheat grown under glasshouse conditions. After 30 days of sowing of wheat under microcosm conditions, 8 zinc transporter (TaZIP) genes were expressed maximally in roots with concomitant accumulation of higher zinc content in bacterially treated plant as compared to the absolute control. Out of four strains tested, two bacteria B. tequilensis CRS-38 and P. nicotinovorans CRS-30 improved seed germination (%), vigor indices (2-2.5 folds), plant biomass, grain yield (2.39 g plant-1) and biofortificated grains (54.25 µg g-1Zn) of wheat. To the best of our knowledge, this may be the first report of presence of zinc solubilization trait in B. glycinifermentans CRS-9, M. oxydans CRS-17 and P. nicotinovorans CRS-30.